PERSEPSI PASIEN DAN KELUARGA TERHADAP ASUHAN KEPERAWATAN YANG DIBERIKAN OLEH MAHASISWA KEPERAWATAN DI RUANG RAWAT INAP RUMAH SAKIT ADVENT BANDUNG - Lina Herliana; Untung Sudharmono (Jurnal Kesehatan, 2020)
The Problem: This research is motivated by the importance of patient perception to improve the dimensions of service quality and nursing care. Method: the study design used descriptive quantitative using percentage calculation. The population in this study was patients who were being treated in inpatient department at Bandung Adventist Hospital, and totaling 30 patients taken with a purposive sampling technique. The survey was conducted using a questionnaire on patient satisfaction with student nursing care consisting of 13 statements Result: Overall, the patient's perception of students nursing care was 87%. This value indicates that nursing care provided by nursing students to patients is in the good category. Even though, if calculated based on each statement, the statement item "students introduce themselves before providing services" has the lowest percentage value of 73%, this value is in the moderate category. Follow up: The results of this study were submitted to the education department, so that nursing students could be guided to maintain and improve the good grades that had been obtained, as well as provide guidance and supervision of the low and low scores obtained.